PENGARUH PROGRAM PRA STUDI TARUNA TERHADAP PERUBAHAN KELINCAHAN TUBUH PADA CALON TARUNA AKADEMI TEKNIK DAN KESELAMATAN PENERBANGAN MAKASSAR - Pateda, Sri Manovita; Taiyeb, Mushawwir; Patellongi, Ilhamjaya; Natzir, Rosdiana; Nawir, Nuchrawi; Badaruddin, Fatmawati (Sainstek, 2012)
This study aims to determine the effect of Precadets Studieson the agility of the bodyon the prospectivecadets Academy of Engineering and Aviation Safety Makassar. The research was conducted on the campus ATKP Makassar. The method used in this study isa prospective observational study approach, to perform an agility examination with a sides tepping tester. Sampling is non random sampling technique by taking as aturated sample. Data were analyzed using statistical analysis by pairedt-testif data were normally distributed, theWilcoxon test the alternative is. The results showed that therate increaseagility by 63% after the implementation of P2ST. Significance test results showed that there P2Steffect the agilityof the body (p =0.002). It was concluded that the implementation of the Pre-Stud y Program cadets give effect to the increased agilityof the body on the prospectivecadets Academy of Engineering and Aviation Safety Makassar.